Searching for Rewards Like a Child Means Less Generalization and More Directed Exploration - Schulz, Eric; Wu, Charley M.; Ruggeri, Azzurra; Meder, Björn (Psychological Science, 2019)
How do children and adults differ in their search for rewards? We considered three different hypotheses that attribute developmental differences to (a) children’s increased random sampling, (b) more directed exploration toward uncertain options, or (c) narrower generalization. Using a search task in which noisy rewards were spatially correlated on a grid, we compared the ability of 55 younger children (ages 7 and 8 years), 55 older children (ages 9–11 years), and 50 adults (ages 19–55 years) to successfully generalize about unobserved outcomes and balance the exploration–exploitation dilemma. Our results show that children explore more eagerly than adults but obtain lower rewards. We built a predictive model of search to disentangle the unique contributions of the three hypotheses of developmental differences and found robust and recoverable parameter estimates indicating that children generalize less and rely on directed exploration more than adults. We did not, however, find reliable differences in terms of random sampling.